Difference in Funding Decision Based on the Growth Potential of the Company in Indonesia - Darmawan, Darmawan; Molla, Edrich (Journal of Economic Development, Environment and People, 2020)
The purpose of the study, The research objective was to To find out the differences in funding decisions between companies that have high growth potential and companies that have low growth potential. Research is a quantitative study. Mean difference test is preceded by Common Factor Analysis to analyze which factors in the Investment Opportunity Set can represent the growth ratio of the company so that it can be used to separate companies with high and low growth potential. Furthermore, the analysis is carried out with a regression model to determine the difference in funding decisions on the growth potential of different companies. The results showed that The consumer goods industry and mining sector sectors that have not proven to be significant are the differences in funding decisions between companies that have the potential to grow high and those with low growth potential. In other sectors, it is evident that there are significant differences in funding decisions between companies that have the potential to grow high and those with low growth potential.